Continuous ambulatory peritoneal dialysis: one year's experience in a UK dialysis unit. Issue 6238 (16th August 1980) - Gokal, R; McHugh, M; Fryer, R; Ward, M K; Kerr, D N
Abstract : Thirty-two patients aged 8-63 years trained to manage themselves by continuous ambulatory peritoneal dialysis for end-stage renal failure achieved better steady-state serum biochemistry and much higher haemoglobin and lower serum phosphate concentrations than during treatment with haemodialysis up to one year before. Two patients, however, returned to intermittent haemodialysis because of recurrent peritonitis. Costs of the technique during the first year were less than half those incurred in the first year of home haemodialysis. Nevertheless, the major advantage was the ease with which patient independence and rehabilitation could be achieved. This technique is an appreciable advance over other forms of management for end-stage renal failure. Nevertheless, until it is more refined and long-term problems have been assessed it should probably be used only in established renal units where back-up treatments are available.